2023
DOI: 10.1108/qrfm-02-2022-0027
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of gender to understand financial behavior. Financial behavior of transgender and cisgender individuals: evidence from India: a qualitative inquiry

Abstract: Purpose This study aims to understand the unique financial behavior of transgender individuals compared to cisgender individuals. Furthermore, this study aims to demonstrate that understanding the financial behavior of transgender people will help financial institutions, regulators and policymakers to include them in the formal financial sector. Design/methodology/approach The qualitative approach to research aims at understanding a given phenomenon among the participants. Semi-structured interviews are cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Thus, good financial literacy can help students live according to their abilities. The results of this study also found exciting facts where gender is related to financial well-being, supported by prior studies which state that women are more prudent in financial behavior than men (Lind et al, 2020;Mundi, 2023), including spending behavior specifically (Abdul Hussein et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, good financial literacy can help students live according to their abilities. The results of this study also found exciting facts where gender is related to financial well-being, supported by prior studies which state that women are more prudent in financial behavior than men (Lind et al, 2020;Mundi, 2023), including spending behavior specifically (Abdul Hussein et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Aparicio et al [ 31 ] stated that bibliometric analysis helps to examine existing literature on a scientific topic. The bibliometric analysis examines keyword, author, and journal statistics [ 32 , 33 ]. The present study highlights the different approaches to treating IDA associated with different disease conditions.…”
Section: Methodsmentioning
confidence: 99%